The New York Public Library science desk reference - Barnes-Svarney, Patricia L. (New York : Macmillan, 1995)
Offers information on scientific theories, meanings of terms, and listings of the major scientists in each field of study and their discoveries.
"A Stonesong Press book.".
Includes bibliographical references and index.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: New York Public Library; New York Public Library; Science -- Handbooks, manuals, etc; Science -- Miscellanea; Science -- Handbooks, manuals, etc; Science -- Miscellanea